Design, evaluation and optimization of microcapsules of leflunomide with EudragitÂ® RL100 and EudragitÂ® RS. 100 by solvent evaporation technique - Pal, Rabindranath; Gupta, Bijan Kumar; Chakraborty, Manas; Debnath, Rabindra (Asian Journal of Pharmaceutics (AJP), 2014)
Leflunomide, an immune modulatory prodrug that is rapidly converted to its active metabolite possibly in the gut wall, plasma and in the liver was microencapsulated by the solvent evaporation technique using a nonaqueous solution of polymethacrylate polymer to achieve its release from the microcapsules at a slower rate. At the optimal condition of process variables such as stirring speed, temperature of the medium, drug polymer ratio and ratio of light liquid paraffin and heavy liquid paraffin, maximum encapsulation efficiency was obtained. These microspheres were free-flowing in nature, discrete and uniform spherical in size, as evident by scanning electron microscopy. The in vitro release experiments were carried out in the simulated intestinal fluid (pH 7.2 phosphate buffer) using united States Pharmacopoeia (USP) XXII apparatus II. The data obtained from the dissolution profiles were compared using different kinetics models and the regression coefficients were compared.